The role of tobacco smoking and illicit drug use in adolescent acute alcohol intoxication - Loes de Veld; Inge M. Wolberink; Joris J. van Hoof; Nico van der Lely (BMC, 2021)
Abstract Background This study aims to determine the prevalence of tobacco smoking and illicit drug use among Dutch adolescents admitted to hospital for acute alcohol intoxication treatment. Furthermore, socio-demographic predictors for smoking and illicit drug use in the sample population will be studied. The relationship between illicit drug use and specific characteristics of intoxication, such as blood alcohol concentration (BAC) and duration of reduced consciousness is also investigated. Methods The national Dutch Paediatric Surveillance Unit was used to prospectively register cases of acute alcohol intoxication from 2007 through 2017. Cases were included if they met the following inclusion criteria: BAC > 0.0 g/L, aged between 10 to 18 years old and requiring hospital treatment due to reduced consciousness. Questionnaires were sent to paediatricians to obtain clinical information. Results During the period 2007-2017, 5322 cases that met the inclusion criteria were reported. In this patient group, the prevalence of tobacco smoking was 22.2% (CI 21.0-23.5%), while the prevalence of illicit drug use was 11.8% (CI 10.9-12.7%). The predictors for smoking were the absence of alcohol-specific parental rule-setting, lower educational level, non-traditional family structure and positive drug screening. The predictors for illicit drug use were the absence of alcohol-specific parental rule-setting and smoking. Illicit drug use was also associated with a lower BAC at the time of admission. Conclusions Assessing smoking and illicit drug use among adolescents admitted for acute alcohol intoxication is important in acute cases of intoxication, for outpatient follow-up and for the purposes of prevention. The relationship between simultaneous illicit drug use and a lower BAC is of relevance for paediatricians' attempts to diagnose acute intoxication. With respect to outpatient follow-up and preventive measures, it is important to be aware that adolescents' alcohol consumption, tobacco and illicit drug use are related and, ultimately, increase the odds of using other substances.